Modeling and Simulation of Multi-Position Linkage Platform for FAO Lines - LIU Jianjian; JIANG Hui; GUO Ning; ZENG Bin; YAN Guoqiang (Chengshi guidao jiaotong yanjiu)
[Objective] To demonstrate various FAO (fully automatic operation) lines operating scenarios under normal and abnormal conditions, help dispatchers and multi-functional teams to conduct relevant job linkage training, analyze and formulate disposal plans for various fault situations and emergency scenarios, and improve emergency disposal capabilities and service levels, it is necessary to study the multi-job linkage platform for FAO lines. [Method] Taking Shanghai Metro Line 15 as an example, based on the modeling and simulation of central dispatching, station control and train operation, one FAO simulation platform is built, and a scenario linkage simulation is carried out to realize joint training and fault emergency response of multi-functional teams. [Result & Conclusion] The constructed multi-position linkage platform can display and analyze actual FAO scenarios, therefore suitable for speciality teaching in professional colleges and joint emergency response drills of rail transit multi-functional teams.